Security politics and techno-securitisation in Star Wars: from the Fall of the Jedi to the Reign of the Empire. Issue 5 (7th December 2022) - Atkinson, Colin
ABSTRACT: The Star Wars franchise – and in particular the 'in-universe' period from the Fall of the Jedi to the Reign of the Empire – represents germane ground for the critical analysis of security in both everyday life and extraordinary circumstances. Although beginning with the films of the 'prequel trilogy' (1999, 2002, 2005) this period has most recently been covered in the animated television series Star Wars: The Bad Batch (2021 –). Deepening the contribution of criminology towards a diverse and critical transdisciplinary field of security studies, this paper conducts a multimodal critical discourse analysis of season one of The Bad Batch . In doing so it describes how, in its depiction of a newly established Imperial regime, the Star Wars franchise has continued to engage with the politics of security through its exploration of the processes and practices of techno-securitisation. The Bad Batch thus acts as an ideological critique of developments in the late-modern securityscape. The discussion section reflects upon how the persistence of politics in the 'Disney era' of Star Wars storytelling, and of security politics in particular, indicates the limits of 'Disneyfication'. The paper concludes by emphasising the value in bridging divides between distinct disciplinary approaches in the study of security.